THE ROLE OF LEGAL MORALITY IN RESOLVING BREACH OF MARRIAGE PROMISE CASES - Tijow, Lusiana Margareth (UNISSULA, 2024)
The concept of the Indonesian rule of law is grounded in the legal ideals of Rechtsidee Pancasila, as articulated in Article 1 paragraph (3) of the 1945 Constitution. This framework establishes Pancasila as the rechtsidee and the ultimate source of all legal authority in Indonesia. Consequently, every statutory regulation must embody and implement the values of Pancasila. The formation of law is not merely a technical process but an imperative moral demand, reflecting the necessity for all individuals to live in accordance with moral principles and just laws. Legal morality posits that the law exists to serve humanity, and when obstacles to justice arise, they must be addressed, whether in theoretical understanding or practical application. In the context of marriage promise cases, the application of legal morality through a restorative justice approach is crucial. This method aims to achieve fair restorative justice, protecting the dignity and honor of women affected by breaches of marriage promises. The law, when applied with moral integrity, convinces the parties involved that it represents the most ethical solution. Restorative justice principles, when applied to marriage promise cases, seek to create a just outcome by providing a win-win solution for both perpetrators and victims. This approach avoids the escalation of conflicts and prevents the accumulation of unresolved cases within the legal system. One of the practical applications of Pancasila values in this context is the emphasis on deliberation and consensus, aiming to achieve justice for all parties involved. Settling disputes through restorative justice, particularly penal mediation, offers a faster, less costly, and more effective resolution compared to conventional civil mediation processes.